Cemented carbide insert with eta phase core

CN117545570BActive Publication Date: 2026-10-27SANDVIK MINING & CONSTR TOOLS AB
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280042928.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-16
Filing Date
2022-06-14
Publication Date
2026-10-27
Estimated Expiration
2042-06-14

AI Technical Summary

Technical Problem

[0005]然而,包含由不含η相的硬质合金表面区域围绕的η相芯并且在所述表面中具有低含量粘结相而在与该η相区域紧邻处具有更高粘结相含量的刀片太脆,从而不能用能够引入更高水平压缩应力的高能表面硬化工序处理

Benefits of technology

[0010]有利地,这些刀片具有高破裂强度和改善的操作性能,并且减少了以前会引起失效的过早刀片崩裂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117545570B_ABST
    Figure CN117545570B_ABST
Patent Text Reader

Abstract

A method of treatment of a cemented carbide insert for rock and mineral cutting, the cemented carbide insert comprising a core of cemented carbide and a surface region of cemented carbide, wherein the core further comprises eta phase and the surface region is free of eta phase, and wherein the mining insert is subjected to a surface hardening procedure, wherein the surface hardening procedure is performed at an elevated temperature above 50°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to carbide inserts for use in rock drilling, mineral cutting, oil drilling, and concrete and asphalt milling. Background Technology

[0002] Cemented carbide possesses a unique combination of high elastic modulus, high hardness, high compressive strength, high wear resistance and abrasion resistance, and good toughness. Therefore, cemented carbide is commonly used in products such as mining tools.

[0003] EP0182759 discloses a cemented carbide body comprising an η-phase-containing cemented carbide core surrounded by a surface region of cemented carbide without the η-phase, and having a low content of binder phase in the surface and a higher content of binder phase immediately adjacent to the η-phase region. The η-phase core exhibits wear resistance and, through gradient bonding with the binder phase, contributes to the toughness of the cutting tool. These cutting tools are highly wear-resistant and resistant to the formation of premature cracking, which leads to premature tool failure.

[0004] It is also known that carbide mining inserts are typically treated with edge deburring and surface hardening processes, such as tumbling, after sintering and centerless grinding. The surface hardening process introduces compressive stress into the mining insert. The presence of compressive stress improves the fatigue resistance and fracture toughness of the mining insert. Therefore, the threshold energy required to fracture the mining insert is higher, thus reducing the likelihood of component chipping, cracking, and / or fracture.

[0005] However, cutting tools containing an η-phase core surrounded by a cemented carbide surface region devoid of the η-phase, and having a low binder phase content in the surface and a higher binder phase content immediately adjacent to the η-phase region, are too brittle to be processed by high-energy surface hardening processes capable of introducing higher levels of compressive stress. While the increase in compressive stress can be achieved by high-energy surface hardening processes, the gains are offset by low yields due to a high proportion of cutting tool breakage and the introduction of micro-damage during processing.

[0006] Therefore, it is desirable to provide a cemented carbide insert with the combined benefits of an η-phase core and an improved component that improves fracture toughness using a method that does not lead to a high level of spalling. Summary of the Invention

[0007] Therefore, this disclosure provides a method for processing a carbide cutting tool for rock drilling and mineral cutting, the carbide cutting tool comprising a carbide core and a carbide surface region surrounding the core, wherein both the surface region and the core contain WC (α phase) and a binder phase (β phase), the binder phase being based on at least one of cobalt, nickel, or iron, and wherein the core further contains an η phase, and the surface region does not contain an η phase, wherein the binder phase content in the inner portion of the surface region immediately adjacent to the core is greater than the nominal content of the binder phase in the carbide body, and the content of the binder phase in the surface region gradually increases in the direction toward the core until it is at least 1.2 times greater than the nominal content of the binder phase in the carbide body, characterized in that the mining cutting tool undergoes a surface hardening process, wherein the surface hardening process is performed at an elevated temperature of 50°C or higher, preferably at a temperature of 100°C or higher, preferably at a temperature of 200°C or higher, more preferably at a temperature between 200°C and 450°C.

[0008] Advantageously, by performing surface hardening treatment at elevated temperatures, it is possible to manufacture inserts with improved fracture toughness without the problem of a high percentage of chipping inserts, where chipping typically occurs in areas with high stress concentration, such as the transition region between a cylinder and a dome and in the bottom of the insert, which would impair manufacturing yield. Using this method, higher levels of compressive stress are introduced into the carbide mining inserts. The elevated tumbling temperature leads to increased toughness of the carbides, so impacts do not cause defects such as microcracks, large surface cracks, or chipping. The combination of higher levels of compressive stress and reduced impact defects improves the fatigue resistance and fracture toughness of the insert, and thus increases insert life. A further advantage of this method is that insert geometries that previously tended to cause excessive damage to corners and therefore had low yields, such as those with small bottom radii, can now be tumbled without causing edge damage. This opens up the possibility of developing insert products with different geometries that were previously unsuitable for tumbling. This method also allows the use of cemented carbide compositions that were previously too brittle for mining applications or high-energy tumbling processes, such as those described in, for example, Epiroc Smith's US7258833B2. The ability to introduce higher levels of compressive stress means that the toughness of the mining blade increases to an acceptable level, thus allowing the use of mining blades with higher hardness, which is beneficial for increased wear resistance and therefore for increased overall blade performance.

[0009] Another aspect of this disclosure is a carbide insert for rock drilling and mineral cutting, the carbide insert comprising a carbide core and a carbide surface region surrounding the core, wherein both the surface region and the core contain a WC (α phase) and a binder phase (β phase), the binder phase being based on at least one of cobalt, nickel, or iron, and wherein the core further contains an η phase, and the surface region does not contain an η phase, wherein the binder phase content in the inner portion of the surface region immediately adjacent to the core is greater than the nominal content of the binder phase in the carbide body, and the binder phase content in the surface region gradually increases in the direction toward the core until it is at least 1.2 times greater than the nominal content of the binder phase in the carbide body, the carbide insert having a profile hardness HV3p and an η phase core hardness HV3η, the profile hardness HV3p being measured at a distance of 0.3 mm from the surface along the non-cylindrical portion at the top of the insert, and the η phase core hardness HV3η being the average of HV3 hardness measurements obtained in the η phase region of the core, characterized in that HV3 p -HV3 η >20, HV3 is preferred p -HV3 η >30, more preferably HV3 p -HV3 η >40, or even more preferably >50.

[0010] Advantageously, these blades have high breaking strength and improved operational performance, and reduce premature blade breakage that previously caused failure.

[0011] Another aspect of this disclosure is a carbide cutting tool for rock drilling and mineral cutting, manufactured according to the methods disclosed above or below. Attached Figure Description

[0012] Figure 1 HV3 is shown. p and HV3 η A diagram showing the location of the indentation.

[0013] Figure 2 HV3 hardness curve. Detailed Implementation

[0014] The cemented carbide body of the present invention has a region at the center of the cemented carbide body in which a finely and uniformly distributed η phase is embedded in a typical α+β phase structure. Simultaneously, the cemented carbide body has a surrounding surface region containing only the α+β phase. Here, the η phase refers to the low-carbon phase of the WC-Co system, such as M6C carbide and M... 12C carbides and a κ phase with an approximate formula M4C. The surface region is completely free of the η phase. The η-phase-free region can be prepared, for example, by adding carbon to a cemented carbide body that contains the η phase at high temperature. By varying the time and temperature, η-phase-free regions of desired thickness can be obtained.

[0015] "Cemented carbide" herein refers to a material comprising at least 50 wt% WC, possibly other hard components common in the field of cemented carbide manufacturing, and preferably one or more metallic binder phases selected from Fe, Co, and Ni. In one embodiment of the method, the cemented carbide mining blade contains a hard phase comprising at least 80 wt%, preferably at least 90 wt% WC.

[0016] The metal binder of cemented carbide may contain other elements that dissolve in the metal binder during sintering, such as W and C derived from WC. Depending on the presence of other types of hard components, other elements may also dissolve in the binder.

[0017] Surface hardening treatment is defined as any treatment that introduces compressive stress into a material through physical impact, resulting in deformation hardening at and below the surface, such as tumbling or shot peening. The surface hardening process is performed after sintering and grinding. Surprisingly, it has been found that surface hardening treatment of mining blades at elevated temperatures reduces or even eliminates carbide-to-carbide impact damage in terms of chipping and microfracture, thus improving product life. The surface hardening process of this invention is performed at an elevated temperature, which is defined herein as the temperature of the mining blade at the start of the surface hardening process. The upper limit of the temperature for performing the surface hardening process is preferably below the sintering temperature, more preferably below 900°C. The temperature of the mining blade is measured by any method suitable for temperature measurement, such as infrared thermography.

[0018] In one embodiment of the invention, the mining blade is surface hardened at a temperature between 150-250°C, preferably between 175-225°C.

[0019] In one embodiment of the present invention, the upper limit of the surface hardening treatment is 700°C, preferably 600°C, and more preferably 550°C.

[0020] In one embodiment of the invention, the mining blade undergoes a surface hardening process at a temperature between 300-600°C, preferably between 350-550°C, and more preferably between 450-550°C.

[0021] The temperature of the mining blades should be measured using any suitable method for measuring temperature. Preferably, an infrared thermometer is used.

[0022] In one embodiment, the cemented carbide comprises a hard component in a metallic binder phase, and wherein the content of the metallic binder phase in the cemented carbide is 4 to 30 wt%, preferably 5 to 15 wt%. The binder phase content needs to be sufficiently high to provide the toughness behavior of the mining blade. The metallic binder phase content is preferably no more than 30 wt%, more preferably no more than 15 wt%. Excessively high binder phase content reduces the hardness and wear resistance of the mining blade. The metallic binder phase content is preferably greater than 4 wt%, more preferably greater than 6 wt%.

[0023] In one embodiment, the metallic binder phase comprises at least 80% by weight of one or more metallic elements selected from Co, Ni, and Fe. Co and / or Ni are preferred, Co is most preferred, and even more preferably 3 to 20% by weight of Co. Optionally, the binder is a nickel-chromium alloy or a nickel-aluminum alloy. Optionally, the cemented carbide mining blade may further comprise a grain refiner compound in an amount of ≤20% by weight of the binder content. The grain refiner compound is suitably selected from the group consisting of carbides, mixed carbides, carbonitrides, or nitrides of vanadium, chromium, tantalum, and niobium. The remainder of the cemented carbide mining blade consists of one or more hard phase components.

[0024] In one embodiment, the cemented carbide further comprises Cr, the amount of Cr being such that the Cr / binder mass ratio is between 0.043 and 0.19, preferably between 0.075 and 0.15, and more preferably between 0.085 and 0.12.

[0025] The Cr / binder mass ratio is calculated by dividing the weight percentage (wt%) of Cr added to the powder blend by the weight percentage (wt%) of the binder in the powder blend, where the weight percentage is based on the weight of that component relative to the total weight of the powder blend. Cr is largely dissolved in the binder phase; however, a certain amount, for example, up to 3% by mass, of undissolved chromium carbides may be present in the cemented carbide body. However, it is preferable to add only Cr up to the Cr / binder mass ratio such that all Cr dissolves in the binder, resulting in a sintered cemented carbide body free of undissolved chromium carbides. If the Cr / binder mass ratio is too low, the positive effect of Cr will be too small. On the other hand, if the Cr / binder mass ratio is too high, the concentration of chromium carbides will increase, and the binder will dissolve in the chromium carbides, thereby reducing the volume of the binder phase and thus making the cemented carbide body too brittle. This invention makes it possible to increase the Cr content before embrittlement becomes a problem.

[0026] Cr is typically added to powder blends in the form of Cr3C2 because this provides the highest proportion of Cr per gram of powder, but it should be understood that alternative chromium carbides (such as Cr3C2) can be used. 26 Cr is added to powder blends by adding C2 or Cr7C3) or chromium nitrides.

[0027] The addition of Cr also improves the corrosion resistance of the cemented carbide body. The presence of Cr also facilitates the conversion of the binder phase from FCC to HCP during drilling, which helps absorb some of the energy generated during the drilling operation. This conversion will thus harden the binder phase during its service life and reduce wear on the buttons. The presence of Cr increases the wear resistance of the cemented carbide and enhances its ability to perform strain hardening.

[0028] In addition to hard phase forming components, binders, and Cr-containing components, there may be incidental impurities in WC-based starting materials.

[0029] In one embodiment, the content of the binder phase in the surface region is increased toward the core to 1.4-2.5 times the nominal content of the binder phase.

[0030] In one embodiment, the grain size of the η phase is 0.5-10 μm.

[0031] In one embodiment, the η-phase content in the core is 2-60% by volume.

[0032] In one embodiment, the width of the η-phase core is 10% to 95% of the diameter of the cemented carbide body.

[0033] In one embodiment, the width of the outermost region with a lower binder phase content is 0.2-0.8 times the width of the region without the η phase.

[0034] In one embodiment, the method includes a step of heating the mining blade and media prior to a surface hardening process, and then performing a surface hardening process on the heated mining blade.

[0035] Mining blades can be heated in a separate step prior to the surface hardening process. Several methods can be used to generate elevated temperatures for the mining blades, such as induction heating, resistance heating, hot air heating, flame heating, preheating on a hot surface, in an oven or furnace, or using laser heating.

[0036] In an alternative implementation, the mining blade remains heated during the surface hardening process. For example, an induction coil is used.

[0037] In one implementation, the surface hardening process is tumbling. Tumbling can be centrifugal or vibratory. A “standard” tumbling process is typically performed using a vibratory tumbling machine (e.g., a Reni Crillo RC 650), where approximately 30 kg of blades are tumbled at approximately 50 Hz for about 40 minutes. An alternative, typical “standard” tumbling process uses a centrifugal tumbling machine (e.g., an ERBA-120) with a closed cap at the top and a rotating disc at the bottom. Another method is a centrifugal drum polishing process. In both centrifugal processes, rotation causes the blades to collide with other blades or with any added media. For “standard” tumbling using a centrifugal tumbling machine, the tumbling operation typically runs from 120 RPM for at least 20 minutes. The liner of the tumbling machine may form oxide or metal deposits on the blade surface.

[0038] The term "body" in this document refers to the innermost part (center) of the cutting tool and, for the purposes of this disclosure, the area with the lowest hardness.

[0039] To introduce a higher level of compressive stress into the carbide mining insert, a high-energy tumbling process can be used. Many different process settings can be used to introduce HET, including the type of tumbling machine, the volume of added media (if any), the processing time, and the process settings, such as the RPM of a centrifugal tumbling machine. Therefore, the most suitable way to define HET is as "any process setting that introduces a specific degree of strain hardening into a homogeneous carbide mining insert of approximately 20 g by mass of WC-Co." In this disclosure, HET is defined as a tumbling treatment that introduces at least the following hardness change (ΔHV3%) as measured using HV3 after tumbling:

[0040] ΔHV3% = 9.72 - 0.00543*HV3 本体 (Equation 1)

[0041] in

[0042] ΔHV3% = 100*(HV3) 0.3mm – HV3 本体 ) / HV3 本体 (Equation 2)

[0043] HV3 本体 HV3 is the average of at least 30 indentation points measured at the innermost (center) part of the carbide mining blade. 0.3mmIt is the average of at least 30 indentation points located 0.3 mm below the tumbling surface of the carbide mining insert. This is based on measurements taken on a carbide mining insert with homogeneous properties. "Homogeneous properties" means that the hardness difference from the surface region to the body region after sintering does not exceed 1%. The tumbling parameters used to achieve the strain hardening described in equations (1) and (2) on a homogeneous carbide mining insert will be applied to a carbide body with gradient properties.

[0044] HET tumbling can typically be performed using an ERBA 120 with a disc size of approximately 600mm. If the tumbling operation is performed without media or with media larger than the blade being tumbled, it operates at approximately 150 RPM; if the media size is smaller than the blade being tumbled, it operates at approximately 200 RPM. A disc size of approximately 350mm can also be used. The FKS04 tumbling machine operates at approximately 200 RPM if the tumbling operation is performed without media or with media larger than the blades being tumbled, or at approximately 280 RPM if the media size is smaller than the blades being tumbled. Typically, the components are tumbled for at least 40-60 minutes.

[0045] In one embodiment, after the mining blade undergoes a surface hardening process at elevated temperatures, a second surface hardening process is performed on the mining blade at room temperature. Advantageously, this removes debris and oxides, such as iron oxides, deposited on the blade surface from the interior of the process container. The second surface hardening process, performed at room temperature, can be carried out under humid conditions, which helps remove dirt and dust from the treated mining blade, thereby reducing health hazards. The second surface hardening process can be high-energy tumbling.

[0046] The lining of the tumbler may need to be modified to withstand the higher temperatures that occur during this process.

[0047] In one embodiment, the surface hardening process is performed under dry conditions.

[0048] In one implementation, all or part of the heat is generated by friction between the blades and any medium added during the tumbling process.

[0049] In one implementation, HV3 η The HV3 value is at least 1450 HV3, preferably at least 1460 HV3, more preferably at least 1470 HV3, more preferably >1490 HV3, and even more preferably >1500 HV3. η It is considered to be the hardness in the η-phase core and is equivalent to the body of the blade.

[0050] Hardness measurements were performed using a KB30S programmable hardness tester from KB Prüftechnik, calibrated against HV1, HV3, HV20, HV30, and HV100 test blocks issued by the Euro Products Calibration Laboratory in the UK. Hardness was measured according to ISO EN6507-01.

[0051] HV3 measurements are performed as follows:

[0052] - Scan the edges of the sample.

[0053] - The hardness tester is programmed to create an indentation at a specified distance from the edge of the sample.

[0054] - Indent at all programmed coordinates with a 3kg load.

[0055] The computer moves the stage to each coordinate, positions the microscope on each indentation, and runs automatic light adjustment, automatic focusing, and automatic measurement of the size of each indentation.

[0056] - Users can check the focus and other interfering results of all indentation photos.

[0057] In one embodiment of the invention, no hard alloy coating is applied.

[0058] Example

[0059] Example 1 - Starting Materials and Tumbling Conditions

[0060] Mining blades with the following composition (as is after sintering) were tested:

[0061]

[0062] Table 1: Composition of the tested mining blades.

[0063] All carbide cutting tools were made using WC powder with a particle size between 5 and 18 μm as measured by FSSS prior to grinding. The WC and Co powders were ground in a ball mill under wet conditions using ethanol and with the addition of 2% by weight polyethylene glycol (PEG 8000) as an organic binder (pressing agent) and carbide grinding media. After grinding, the mixture was spray-dried in a N2 atmosphere, and then, for samples A, C, and D, uniaxially pressed into mining cutting tools with an outer diameter (OD) of approximately 18 mm, a height of approximately 32 mm, and a weight of approximately 54 g, each tool having a spherical dome (“cutting edge”) at the top. Sample B had an OD of 10 mm. The cutting tools were then pre-sintered in N2 gas and subsequently heat-treated in a carburizing atmosphere. After sintering, the samples had an η-phase content of approximately 4% by weight in the η-phase core. An example of the sintering method is further detailed in EP0182759.

[0064] Comparative sample A was wet-tumbled at room temperature using a standard centrifugal tumbler (i.e., low-energy, non-HET). Comparative sample B was wet-tumbled at room temperature using a HET method.

[0065] For invention samples C and D, a "hot shaking" method was used to replicate HET at elevated temperatures on a laboratory scale. This hot shaking method uses the trademark Corob. TMThe commercially available paint shaker, Simple Shake 90, has a maximum load of 40 kg and a maximum shaking frequency of 65 Hz. The "hot shaking" method is performed on batches of 20 mining blades at a frequency of 45 Hz. Approximately 1000 grams or 50 blades and 4.0 kg of carbide media (1490 balls approximately 7 mm in diameter) are placed in a cylindrical steel container with an inner diameter of 10 cm and an inner height of 12 cm, filling it to 2 / 3 of its height. The steel container containing the mining blades is heated in a furnace with the media to a raised temperature of 300°C, and the mining blades are held at this target temperature for 120 minutes. After heating, the steel container is immediately transferred to the paint shaker and shaken for 9 minutes immediately. The transfer time between the furnace and the start of the shaker is less than 20 seconds. The media is made of H10F grade cemented carbide with 10 wt% Co, 0.5 wt% Cr, and 89.5 wt% WC, resulting in a sintered HV20 of approximately 1600. In the results table, samples treated according to this method are referred to as “300°C dry shaking,” where shaking is performed under dry conditions, i.e., no water is added to the shaking. Then, both cases (C and D) of the present invention undergo a second tumbling step under wet conditions at room temperature, but with different tumbling intensities. For sample C, the second tumbling step uses the same conditions as the hot shaking method described above, except that no heating or furnace step is performed before shaking, and 100 mL of water is added to the steel cylinder before tumbling to achieve a near-room temperature, wet, and very strong tumbling effect. For sample D, the second tumbling step is performed for 50 minutes under wet conditions at 300 RPM (close to the maximum RPM) using a standard Rasler FKS04 centrifugal tumbling machine with a disc size of 350 mm.

[0066] The temperature used for surface hardening treatment is the starting temperature. For batch processing at a starting temperature of 25°C, if water is added to the process, the temperature is not expected to increase significantly as the samples are processed.

[0067] Example 2 - Edge Damage

[0068] Importantly, the damage to the edges of the mining blades after tumbling should be minimal, preferably nonexistent, to achieve the highest yield.

[0069] After tumbling, damage was visually inspected in batches of 20 cutting tools of each sample type to compare the yield of good-quality mining cutting tools when surface hardening was performed at room temperature and higher temperatures. A mining cutting tool was considered damaged if the length of the chipping was greater than approximately 1 mm, or if the chipping extended to the centerlessly ground cylindrical surface of the tool. The percentage of damaged cutting tools is reported in Table 2:

[0070] A (Comparison) 3% B (Comparison) 99% C (Invention) 5% D (Invention) 5%

[0071] Table 2: Percentage of mining blades damaged after shaking treatment.

[0072] The results in Table 2 show that the edge damage of the mining blades is reduced when the surface hardening process is carried out at elevated temperatures. The results in Table 2 also indicate that the edge damage percentage of sample B blades is very high, making it a process not feasible for production, while for inventive samples C and D, the yields are comparable to those achieved using standard centrifugal tumbling.

[0073] Example 3 - Blade Compression Test

[0074] The cutting tool compression test method involves compressing a drill bit between two parallel, hard, opposing surfaces at a constant displacement rate until the bit fails. A test fixture based on the ISO 4506:2017(E) standard "Hardmetals – Compression test" is used, with a carbide anvil having a hardness exceeding 2000 HV, while the test method itself is adjusted to be suitable for testing the toughness of rock drilling tools. The fixture is mounted on an Instron 5989 test frame.

[0075] The loading axis is the same as the rotational symmetry axis of the blade. The opposing surfaces of the fixture meet the parallelism requirements of ISO 4506:2017(E), i.e., a maximum deviation of 0.5 μm / mm. The blade under test is loaded at a constant crosshead displacement rate of 0.6 mm / min until failure, while the load-displacement curve is recorded. Before test evaluation, the compliance of the test equipment (rig) and test fixture is subtracted from the measured load-displacement curve. Five blades are tested for each sample type. Damage to the opposing surfaces is checked before each test. Blade failure is defined as a sudden drop in the measured load of at least 1000 N. Subsequent inspection of the blades under test confirmed that this was consistent with the occurrence of macroscopically visible cracks in all cases. Material toughness is characterized by the total absorbed strain energy until fracture. The total fracture energy required to crush the sample is expressed in Joules (J) in Table 3 below:

[0076] A (Comparison) 13.1 C (Invention) 29.0 D (Invention) 23.7

[0077] Table 3: Fracturing energy (J) required to crush the sample

[0078] Table 3 shows that fairly high fracture toughness was achieved from the invention samples C and D.

[0079] Example 4 - Hardness Measurement

[0080] HV3 hardness was measured on the cross-section of a polished blade at depths of 0.3, 0.8, 1.3, 1.8, 2.3, 2.8, 3.3, 3.8, 4.3, 4.8, 5.3, 5.8, 6.3, and 6.8 mm below the edge. Figure 1 The hardness indentation location and hardness measurements of sample C are shown. The profile hardness HV3p is the average of HV3 hardness measurements taken 0.3 mm below the surface of the non-cylindrical portion at the top of the cross-blade after tumbling, as shown... Figure 1 As shown. The core hardness HV3η of the η phase is the average value of the HV3 hardness measurements obtained in the core η phase region, such as... Figure 1 As shown in Table 4, the average HV3η measurements are summarized, and it is shown that for the inventive sample, HV3p-HV3η is larger.

[0081]

[0082] Table 4: Hardness difference between profile hardness and core hardness.

[0083] Figure 2 The HV3 profile, from the tip to the bottom through the center of the blade, was shown using Origin software from OriginLab.

[0084] Example 4 - Field Test

[0085] For DP65 with 18mm TM Down-the-hole (DTH) rock drill bits with cutting edges Tests were conducted in which the cutting inserts were treated with either cold, wet high-energy tumbling (Sample B – Comparative Sample) or dry, hot high-energy tumbling at 300°C (Sample C – Invention Sample). The tumbling of both sets of inserts was performed in the same equipment under identical conditions (e.g., tumbling intensity and tumbling time). The comparative sample was tumbled in a steel tumbling drum using approximately 5 kg of carbide inserts and 100 mL of water-based grinding fluid, according to industry standards. The invention sample underwent high-energy tumbling directly by preheating approximately 5 kg of carbide inserts, including a steel tumbling drum, to 300°C, and then placing the filled, hot tumbling drum into the tumbling machine.

[0086] Each DTH drill bit has 12 inserts with a height of 32.5 mm and a weight of 108 g in the outermost gage insert row, and 17 inserts with a height of 27.5 mm and a weight of 89 g in the remaining front side.

[0087] The drill bit was tested on rock primarily composed of diorite and diabase, where the compressive strength ranged from 280 to 350 MPa. Diabase is harder than diorite, which typically leads to many bit failures, especially at the gauge cutter, the weakest point of the rock drill bit. Improved gauge cutter strength will result in improved tool life in terms of drilling meters.

[0088] Eight comparative samples and nine inventive samples were tested. The results are shown in Table 5 below.

[0089]

[0090] Table 5: Summary of Field Test Results

[0091] It can be seen that the average drill bit life increased from 482m to 557m, an increase of 16%, and the average number of gauge insert failures decreased from 7.5 to 5.9, a reduction of 21%.

Claims

1. A method for processing a carbide insert for rock drilling and mineral cutting, the carbide insert comprising a carbide core and a carbide surface region surrounding the core, wherein both the surface region and the core contain an α phase of WC and a β phase of a binder phase, the binder phase being based on at least one of cobalt, nickel, or iron, and wherein the core further contains an η phase, and the surface region does not contain the η phase, wherein the binder phase content in the inner portion of the surface region immediately adjacent to the core is greater than the nominal content of the binder phase in the carbide insert, and the content of the binder phase in the surface region gradually increases in the direction toward the core until it is at least 1.2 times the nominal content of the binder phase in the carbide insert; wherein the insert undergoes a surface hardening process; characterized in that, The carbide cutting tool is heated to a temperature above 50°C before the surface hardening process; then the surface hardening process is performed at an elevated temperature above 50°C and below 900°C, and wherein the surface hardening process is tumbling.

2. The method of claim 1, wherein the cemented carbide comprises a hard component in a metal binder phase, and wherein the content of the metal binder phase in the cemented carbide is 3 to 30% by weight.

3. The method according to claim 2, wherein the metal binder phase comprises at least 80% by weight of one or more metal elements selected from Co, Ni and Fe.

4. The method according to claim 1 or 2, wherein the cemented carbide further comprises Cr, the amount of Cr being such that the mass ratio of Cr to the binder phase is 0.043-0.

19.

5. The method according to claim 1 or 2, wherein the content of the binder phase in the surface region increases toward the core to 1.4-2.5 times the nominal content of the binder phase of the cemented carbide cutting tool.

6. The method according to claim 1 or 2, wherein the blade is tumbled together with the medium, and wherein the medium is also heated to a temperature of 50°C or higher before and during tumbling.

7. The method according to claim 1 or 2, wherein the carbide insert is kept heated during the surface hardening process.

8. The method according to claim 1 or 2, wherein after the carbide insert undergoes the surface hardening process at an elevated temperature, the carbide insert undergoes a second surface hardening process at room temperature.

9. The method according to claim 1 or 2, wherein, The tumbling process is a "high-energy tumbling" process, in which the homogeneous carbide cutting tool undergoes deformation hardening after tumbling, thus... HV3%≥9.72-0.00543 HV3 本体 ,in HV3% represents the change in hardness. HV3% = 100 (HV3 0.3mm – HV3 本体 ) / HV3 本体 HV3 本体 HV3 is the average of at least 30 indentation points measured at the innermost part of the carbide insert. 0.3mm It is the average of at least 30 indentation points located 0.3 mm below the tumbling surface of the carbide cutting tool.

10. The method according to claim 1 or 2, wherein the surface hardening process is performed under dry conditions.

11. A carbide cutting tool for rock drilling and mineral cutting manufactured by the method according to any one of claims 1-10.

Citation Information

Patent Citations

  • Cemented carbide body used preferably for rock drilling and mineral cutting

    EP0182759A1

  • High-energy cascading of abrasive wear components

    US7258833B2

  • Hard alloy suitable for drilling rock and cutting ore

    CN85108173A